Short carbon fibre-reinforced epoxy foams with isotropic cellular structure and anisotropic mechanical response produced from liquid foam templates - Song,W; Konstantellos,G; Li,D; Lee,K-Y (Composites Science and Technology, 2019)
In this work, we show that mechanically anisotropic short carbon fibre (sCF)-reinforced epoxy foams with an isotropic cellular structure can be fabricated from liquid foam templates. Short carbon fibres were mechanically frothed in an uncured liquid epoxy resin to produce an air-in-resin liquid foam template, followed by subsequent polymerisation. Fracture toughness test showed that the incorporation of short carbon fibres into the epoxy foams led to a significant increase in their critical stress intensity factors. It was also observed that neat epoxy foams failed catastrophically whilst sCF-reinforced epoxy foams failed in a progressive manner. Compression test further showed that the in-plane compressive moduli of the mechanically frothed sCF-reinforced epoxy foams were significantly higher than their out-of-plane compressive moduli, signifying an anisotropic mechanical response. This anisotropic mechanical response stemmed from the radial flow generated by the high intensity mechanical frothing process, facilitating the preferential orientation of the added short carbon fibres in-plane whilst the entrained air bubbles during the mechanical frothing process were in equilibrium with the surrounding uncured liquid epoxy resin, resulting in an epoxy foam with an isotropic (spherical) cellular structure.